Rare phytomyxid infection on the alien seagrass Halophila stipulacea in the southeast Aegean Sea - VOHNÍK, MARTIN; BOROVEC, ONDŘEJ; ÖZBEK, ELIF ÖZGÜR; OKUDAN ASLAN, EMINE ŞÜKRAN (Mediterranean Marine Science, 2018)
Phytomyxids (Phytomyxea) are obligate endosymbionts of many organisms such as algae, diatoms, oomycetes and higher plants including seagrasses. Despite their supposed significant roles in the marine ecosystem, our knowledge of their marine diversity and distribution as well as their life cycles is very limited. Here we describe anatomy and morphology of several developmental stages of a phytomyxid symbiosis recently discovered on the petioles of the alien seagrass Halophila stipulacea (Forssk.) Asch. at a locality in the southeast Aegean Sea. Its earliest whitish stages appeared already on the youngest leaves at the apex of the newly formed rhizomes. The infected host cells grew in volume being filled with plasmodia which resulted in the formation of characteristic macroscopic galls. The plasmodia eventually cleaved into spores and in the final stage recorded by us, the dark brown to black galls contained mature resting spores often occurring in duplexes and possessing thick verrucous outer walls. Based on its anatomo-morphological features the phytomyxid was assigned as Plasmodiophora cf. halophilae. Little is so far known about the origins and eco-physiological functioning of this rare symbiosis. However, seemingly similar infection patterns were reported in 1913 on Halophila ovalis (R. Br.) Hook. f. from Java and in 1995 on H. stipulacea from Sicily. Since H. stipulacea is of the Indo-Pacific origin and no phytomyxid infection was observed on the co-occurring autochthonous seagrass Cymodocea nodosa, we hypothesize that its phytomyxid might have co-migrated into the Mediterranean through the Suez Canal, potentially reaching as far as the southern Ionian Sea.